2021
DOI: 10.3389/fpls.2021.771276
|View full text |Cite
|
Sign up to set email alerts
|

Food Processing Technologies to Develop Functional Foods With Enriched Bioactive Phenolic Compounds in Cereals

Abstract: Cereal grains and products provide calories globally. The health benefits of cereals attributed to their diverse phenolic constituents have not been systematically explored. Post-harvest processing, such as drying, storing, and milling cereals, can alter the phenolic concentration and influence the antioxidant activity. Furthermore, cooking has been shown to degrade thermo-labile compounds. This review covers several methods for retaining and enhancing the phenolic content of cereals to develop functional food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 202 publications
0
16
0
Order By: Relevance
“…Miso has received considerable attention as a potential approach to reduce the risk of chronic illness, such as cardiovascular disease, and its long-term consumption has also been associated with a possible lower risk of mortality [ 19 ]. Recent studies have reported the possible utilization of food by-products, such as grain brans, and their solid-state fermentation by fungus, in order to develop functional foods, enhanced in bioactive compounds [ 20 ]. The fungal fermentation of legume-based foods in cereal bran substrates has been suggested as it may enhance the phenolic and carotenoids bioavailability, leading to increased antioxidant activity and exhibiting protective effects against cardiovascular disease [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Miso has received considerable attention as a potential approach to reduce the risk of chronic illness, such as cardiovascular disease, and its long-term consumption has also been associated with a possible lower risk of mortality [ 19 ]. Recent studies have reported the possible utilization of food by-products, such as grain brans, and their solid-state fermentation by fungus, in order to develop functional foods, enhanced in bioactive compounds [ 20 ]. The fungal fermentation of legume-based foods in cereal bran substrates has been suggested as it may enhance the phenolic and carotenoids bioavailability, leading to increased antioxidant activity and exhibiting protective effects against cardiovascular disease [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, wheat malt is considered for the production of top‐fermenting flavourful beer. This bioprocessing technique has been found to increase the phenolic content by generating new phenolic‐derived metabolites (Kasote et al ., 2021). The malting process typically involves steeping, germinating, and kilning.…”
Section: Malting and Germinationmentioning
confidence: 99%
“…In cereals, a first significant decay of bioactive compounds is observed after traditional milling with a significant amount of antioxidant lost with the bran [185,186]. Strategies to enhance the antioxidant potential of flours are the emerging techniques based on alternative milling methods (micronization, and microfluidization) [187,188] or dedicated fractionation processes (debranning/pearling and air-classification) to select fractions rich in phytochemicals of the external grain layers [182,189,190]. The level of bioactive compounds is further affected by processing and cooking [191].…”
Section: Impact Of Crop Management and Food Processing On Antioxidant...mentioning
confidence: 99%